Study of magnetism and electrocatalytic properties in perovskite DyCrO3 - Ughade, Supriya; Singh, Dinesh; Poddar, Pankaj (Journal of Alloys and Compounds, 2025)
Uniformly sized perovskite DyCrO3 was synthesized by facile hydrothermal method. Complex interdependence of various parameters such as - pH, crystal growth duration, reaction temperature, precursor, and capping molecules on crystal growth was extensively investigated. The effect of synthesis parameters on the magnetic properties of hydrothermally synthesized DyCrO3 was compared with high-temperature synthesized DyCrO3. DyCrO3's potential for electrocatalytic water splitting in an alkaline medium (1.0 M KOH) was also evaluated. It demonstrates an overpotential of 280 mV for oxygen evolution reaction (OER) and 210 mV for hydrogen evolution reaction (HER). Further, it exhibits promising stability for OER and HER.
Keywords: DyCrO3; Electrocatalytic water splitting; Hydrothermal synthesis; magnetic property; perovskite